INDUSTRIALIZATION OF WHITE OYSTER MUSHROOM CULTIVATION (PLEUROTUS OSTREATUS) AS A STRATEGIC SOLUTION TO ADDRESS STUNTING IN WINDUAJI VILLAGE, PAGUYANGAN DISTRICT, BREBES REGENCY - Yunida Triana, Noor; Saraswati, Esti; Wirakhmi, Ikit Netra; Ningrum, Ema Wahyu; Lestari, Sri; Ratnaningtyas, Nuniek Ina; Wati, Erna Kusuma (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Stunting is a chronic malnutrition problem caused by inadequate nutritional intake over an extended period. Winduaji Village is classified as an area of extreme poverty with a high prevalence of stunting determinants. There is a need for information dissemination on stunting. The methods used include education on stunting, parenting practices, positive coping, behavioral change communication, and training on creating food products from processed mushrooms, dry cakes, wet cakes, and business management. The target audience consists of 21 community health cadres from Rumah Desa Sehat (RDS) and 60 families in extreme poverty. The goal of the activity is to improve the skills of RDS cadres in assisting impoverished families and to increase their knowledge about stunting prevention efforts, as well as to enhance their ability to develop businesses using processed oyster mushrooms. This activity is part of the Kosabangsa program by DRTPM Ristek Dikti in 2024, conducted from September to November 2024 in Winduaji Village, Paguyangan District, Brebes Regency. The results show an increase in RDS cadres’ knowledge of stunting, behavior change communication, and business management. Families in extreme poverty gained understanding of stunting prevention measures and became able to practice making supplementary foods from processed oyster mushrooms, dry cakes, and wet cakes. An evaluation of this activity needs to monitor the outcomes to ensure the Kosabangsa program positively impacts impoverished communities with stunted children.